REPAIR OF OLD STOCK COW LEATHER UPPER SHOES USING REFINISHING TECHNIQUES - Sofwan Siddiq Abdullah; Anggoro Tri Hatmanto; Nais Pinta Adetya; Nur Mutia Rosiati (Politek ATK Yogyakarta Press, 2023)
Finished skin for a long time will accumulate, overgrown mold, unpleasant odor, folds occur, uneven color and potentially damaged skin. This study aims to increase the optimality use of cowhide upper shoe articles of old stock cattle by refinishing techniques. The advantage of refinishing is the shorter process time than reprocessing, wet processing and continues refinishing. The stages are sorting, grading, preliminary test, refinishing treatment and final testing. Materials used are three pieces of leather that consist fullgrain nappa, softy mill nappa and correctedgrain. Nappa softy mill skin requires mechanical toggling treatment because there are fold defects. Fullgrain and correctedgrain nappa leathers are immediately refinished. The analysis was organoleptical and physical analysis. Physical tests involve tensile strength, elongation, tear resistance, wet and dry rubbing resistance [4]. The results of physical tests of tear strength, elongation and tensile strength show that refinishing does not change much about the character of leather. The results of physical tests of tear strength, elongation and tensile strength showed that refinishing doesn’t change the character of leather. The refinishing process successfully increases the rubbing resistance of both dry and wet paints and organoleptically improves the quality of leather.